Research progress on the role of microbiota in the pathogenesis of gallstone disease - Liu, Yuntian; Yao, Bihui; Yang, Xiaoqin; Sun, Qi; Yang, Xusheng; Liang, Lu (Frontiers in Microbiology, 2025)
Gallstone disease (GSD) is a prevalent digestive disorder traditionally believed to stem from disturbances in cholesterol metabolism and imbalances in bile composition. Recent evidence highlights a shift in understanding GSD from a primarily metabolic disorder to a microbial-mediated pathology. The biliary tract, rather than a sterile environment, may harbor a distinct microbial community that, under homeostatic conditions, may coexist with the host to maintain biliary health. Disruption of this equilibrium can initiate GSD. Gut microbiota contributes to GSD by modulating enterohepatic circulation via the FXR-FGF15 pathway and producing metabolites, including β-glucuronidase, that promote cholesterol precipitation. Biofilm formation by biliary microbes further enhances nucleation and gallstone formation. Recent studies have characterized biliary microbial communities but are limited by small sample sizes, methodological heterogeneity and scant mechanistic insight. These limitations impede translation into clinical practice. Despite these limitations, accumulating evidence underscores the potential of targeting biliary and intestinal microbiota in GSD prevention and therapy. This review integrates current evidence to elucidate microbiota-mediated mechanisms and translational opportunities, offering an innovative perspective for preventive and therapeutic strategies.